Privacy Secure Data Authentication in Cloud Computing - Sarang, Rakesh Prasad; Chaturvedi, Anshu; Goswami, D.N (International Journal of Computer Sciences and Engineering, 2025)
Cloud computing is a new modern and broad concept of the world. Users store huge amount of data on cloud storage for future use. Now a day’s privacy to the data stored in cloud is an aspect and security is a very major challenging mission in cloud computing. These challenges have huge effect in the development of secure data storage qualities of cloud system. The objective of this paper is to provide the privacy two factor authentication (2FA) techniques algorithm for the cloud environment with an attempt to bring solutions of such problems. The main aim of this paper is to design and propose TwoFactor Authentication (2FA) technology with One-Time Password (OTP) and finger print for providing strong security system to the data stored in cloud system. This paper, presents two modules, the first module deals with ensuring the storing security of data in encrypted format by using the (2FA) technique and the second module with digital signature algorithm (DSA). We have proposed framework which provides, verifies user authenticity using two-step verification, which is based on password, CSP level key establishment between the users and the cloud server.